2001
DOI: 10.1046/j.1471-4159.2001.00131.x
|View full text |Cite
|
Sign up to set email alerts
|

A cGMP‐dependent protein kinase is implicated in wild‐type motility in C. elegans

Abstract: In mammals, cyclic GMP and cGMP-dependent protein kinases (cGKs) have been implicated in the regulation of many neuronal functions including long-term potentiation and long-term depression of synaptic ef®cacy. To develop Caenorhabditis elegans as a model system for studying the neuronal function of the cGKs, we cloned and characterized the cgk-1 gene. A combination of approaches showed that cgk-1 produces three transcripts, which differ in their ®rst exon but are similar in length. Northern analysis of C. eleg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
26
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 66 publications
2
26
0
Order By: Relevance
“…The gcy-12 mutations, as well as the egl-4 mutations, were classified as class I suppressors, indicating that the che-2 mutation causes the small-body phenotype through altered GCY-12 function. Biochemical analyses showed that EGL-4 indeed requires cGMP for its kinase activity (Stansberry et al 2001;Hirose et al 2003); therefore, the simplest interpretation is that GCY-12 is the guanylyl cyclase that provides cGMP to EGL-4 in the pathway regulating body size. The studies of this article provide several lines of evidence to support this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The gcy-12 mutations, as well as the egl-4 mutations, were classified as class I suppressors, indicating that the che-2 mutation causes the small-body phenotype through altered GCY-12 function. Biochemical analyses showed that EGL-4 indeed requires cGMP for its kinase activity (Stansberry et al 2001;Hirose et al 2003); therefore, the simplest interpretation is that GCY-12 is the guanylyl cyclase that provides cGMP to EGL-4 in the pathway regulating body size. The studies of this article provide several lines of evidence to support this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in egl-4 result in the class I Chb phenotype and the expression of egl-4 cDNA in several sensory neurons can rescue this phenotype (Fujiwara et al 2002). The EGL-4 kinase is activated by cGMP (Stansberry et al 2001;Hirose et al 2003); therefore, it is conceivable that cGMP produced by the GCY-12 guanylyl cyclase activates EGL-4 in vivo. To examine this possibility by genetic analyses, we first made a gcy-12;egl-4 double mutant.…”
Section: Genetic Interaction Between Gcy-12 and Egl-4mentioning
confidence: 99%
See 1 more Smart Citation
“…3C). Two allosteric cGMP-binding domains are present in the amino one-half of EGL-4 (29,30). In other PKGs, cGMP binding has been shown to relieve an inhibitory interaction between an amino terminal pseudosubstrate region and the kinase domain (31).…”
Section: Percent Nuclear Gfp-egl-4 Per Unit Time At Each Time Interval)mentioning
confidence: 99%
“…All three mammalian PKG isoforms (I␣, I␤, and II) contain a leucine zipper motif in this sequence, although the remainder of the residues in the sequence have limited sequence identity. Other eukaryotic PKGs such as the two Drosophila PKGs (28) and the PKGs found in Caenorhabditis elegans (29), Hydra oligactis, and Apis mellifera (30) also contain a leucine zipper motif in this region (see Fig. 1).…”
mentioning
confidence: 99%